(untitled) (Journal of the College of Basic Education, 2022)
The present study is on the optoelectronic properties of CdTe/Si heterojunction photodetector made by deposition of CdTe by flash evaporation technique on clean monocrystalline phase of Si. Electrical and structural properties of grown CdTe film were investigated. The CdTe/Si junction exhibits fair diode rectification and the soft breakdown occurred at VB>2 V. Dark I–Vcharacteristics of the CdTe/Si photodetector are examined at room temperature.